'Enjoying the kick': Locating pleasure within the drug consumption room - Duncan, T.; Duff, Cameron; Sebar, B.; Lee, J. (Elsevier BV, 2017)
© 2017 Elsevier B.V. Background: Harm reduction policy and praxis has long struggled to accommodate the pleasures of alcohol and other drug use. Whilst scholars have consistently highlighted this struggle, how pleasure might come to practically inform the design and delivery of harm reduction policies and programs remains less clear. The present paper seeks to move beyond conceptual critiques of harm reduction's 'pleasure oversight' to more focused empirical analysis of how flows of pleasure emerge, circulate and, importantly, may be reoriented in the course of harm reduction practice. Methods: We ground our analysis in the context of detailed ethnographic research in a drug consumption room in Frankfurt, Germany. Drawing on recent strands of post-humanist thought, the paper deploys the concept of the 'consumption event' to uncover the manner in which these facilities mediate the practice and embodied experience of drug use and incite or limit bodily potentials for intoxication and pleasure. Results: Through the analysis, we mapped a diversity of pleasures as they emerged and circulated through events of consumption at the consumption room. Beyond the pleasurable intensities of intoxication's kick, these pleasures were expressed in a range of novel capacities, practices and drug using bodies. In each instance, pleasure could not be reduced to a simple, linear product of drug use. Rather, it arose for our participants through distinctive social and affective transformations enabled through events of consumption at the consumption room and the generative force of actors and associations of which these events were composed. Conclusion: Our research suggests that the drug consumption room serves as a conduit through which its clients can potentially enact more pleasurable, productive and positive relations to both themselves and their drug use. Acknowledging the centrality of pleasure to client engagement with these facilities, the paper concludes by drawing out the implications of these findings for the design and delivery of consumption room services.